Oral microbiota: the overlooked catalyst in cancer initiation and progression - Wang, Xinlin; He, Xin; Zhong, Bin (Frontiers in Cell and Developmental Biology, 2025)
The advancement of high-throughput sequencing technology in recent decades has led to a greater understanding of the components of the oral microbiota, providing a solid foundation for extensive research in this field. The oral microbiota plays an important role in an individual’s overall health. It has been shown to be significantly correlated with chronic human diseases, including diabetes, rheumatoid arthritis, cardiovascular disease, periodontal disease, and Alzheimer’s disease. Furthermore, tumor occurrence and development are closely related to the oral microbiome. Specific bacteria, such as Fusobacterium nucleatum (F. nucleatum), Porphyromonas gingivalis (P. gingivalis), Streptococcus, Streptomyces, Prevotella, and Fibrophagy gingivalis, play critical roles in cancer development. The oral microbiota has various oncogenic mechanisms, including bacterial inflammation, immunological suppression, tumor growth mediated by bacterial toxins, antiapoptotic activity, and carcinogenic effects. This paper reviews the role of the oral microbiota in the occurrence and progression of cancer and systematically elucidates the molecular mechanisms by which dysbiosis influences tumorigenesis and tumor progression. This information can provide a theoretical basis for exploring cancer treatment strategies and offer new insights for cancer prevention.